Xanthogranulomatous Oophoritis: A Rare Case Report - Kaneeka Bhatnagar; Vikram Narang; Bhavna Garg; Neena Sood (Iranian Society of Pathology, 2018)
Background and Objective: Xanthogranulomatous oophritis is an uncommon, non-neoplastic, chronic process in which the affected organ is destroyed by massive cellular infiltration of foamy histiocytes admixed with multinucleated giant cells, plasma cells, fibroblasts, neutrophils, and foci of necrosis. The etiology of this entity is unknown, but it shares histopathological findings similar to those of xanthogranulomatous change occurring in various organs, including the gallbladder and kidney.Case Report: The current case was a 20-year-old female presenting with a tubo-ovarian mass with suspicion of malignancy on clinicoradiological findings and final diagnosis of xanthogranulomatous oophritis established on histopathology.Conclusion: Clinically and radiologically, xanthogranulomatous oophritis mimics tumor of the ovary and fallopian tube, thereby making it an important entity. A vigilant histopathological evaluation is important to diagnose the disease.